2005
DOI: 10.3748/wjg.v11.i32.4986
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect ofAstragalus membranaceuson intestinal mucosa reperfusion injury after hemorrhagic shock in rats

Abstract: High dose Astragalus membranaeus has much better protective effect on hemorrhagic shock-reperfusion injury of intestinal mucosa than low dose Astragalus membranaceus. The mechanism may be that Astragalus membranaceus can improve antioxidative effect and regulate NO/ET level during hemorrhagic reperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 26 publications
0
24
0
1
Order By: Relevance
“…Astragalus membranaceus is widely used for prevention of ROS-mediated injury in pathological situation through its antioxidant properties. 13,[31][32][33] In an in vitro study, it was demonstrated by electron paramagnetic resonance imaging technique that Astragalus membranaceus can potently inhibit ROS produced by the dimethyl sulphoxide system and scavenge over 90% of ROS. 34) Recently, the emerging experiments reported that a herbal formulation, comprising Astragalus membranaceus, improved the pancreatic beta cell function via the antioxidative effect.…”
Section: Discussionmentioning
confidence: 99%
“…Astragalus membranaceus is widely used for prevention of ROS-mediated injury in pathological situation through its antioxidant properties. 13,[31][32][33] In an in vitro study, it was demonstrated by electron paramagnetic resonance imaging technique that Astragalus membranaceus can potently inhibit ROS produced by the dimethyl sulphoxide system and scavenge over 90% of ROS. 34) Recently, the emerging experiments reported that a herbal formulation, comprising Astragalus membranaceus, improved the pancreatic beta cell function via the antioxidative effect.…”
Section: Discussionmentioning
confidence: 99%
“…This herb has demonstrated high antioxidant activity in protecting against intestinal mucosal reperfusion injury in rats. 26 Because this was an in vivo study, it is possible that antioxidant activity was modified within the whole animal. Although we have analyzed the lipophilic and hydrophilic radical-quenching capacity using the ORAC assay, which has been found to be the most relevant for biologic samples, 27 limitations of in vitro antioxidant assays include the fact that they do not account for bioavailability, retention of antioxidants by tissues, and reactivity in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Medicinally, AR is used as a diuretic and tonic herb in many Asian countries, to enhance physical strength and endurance, strengthen the immune system, lower blood pressure, and promote excretion and circulation (Zhao et al, 1990;Sheng et al, 2001;Yu et al, 2006). Clinically, AR is used to treat chronic phlegmatic disorders and general gastrointestinal disturbances including stomach ulcers and diarrhea (Yang, 1993;Hei et al, 2005).…”
Section: Introductionmentioning
confidence: 99%